Prevalence of breakthrough chemotherapy-induced nausea vomiting in patients on highly emetogenic chemotherapy: A Single-center observational study - Lokkur, Pooja; Mahanta, Neelakshi; Kalita, Naba; Deka, Hitesh; Kutum, Niharika; Ray, Arpita (Oncology Journal of India, 2021)
Introduction: Chemotherapy-induced nausea and vomiting (CINV) is a distressing side-effect of cancer chemotherapy which may lead to noncompliance with treatment or delay in treatment. Breakthrough nausea and vomiting is the current unmet need in the management in of CINV. Objectives: The present study was planned to determine the prevalence of breakthrough CINV in patients on highly emetogenic chemotherapy (HEC) and to evaluate the need for rescue medications in them. Materials and Methods: The present observational study was conducted on chemotherapy-naive patients, who were scheduled to receive HEC. The patients who received at least 2 cycles of HEC over a 1-year study period enrolled as a study sample. All patients were subjected to a questionnaire which consists of the demographic details, details of disease and prescribed chemotherapy, and probable risk factors for CINV. The severity of nausea vomiting was calculated using the Multinational Association of Supportive Care in Cancer antiemetic tool. The incidence of breakthrough nausea vomiting was assessed and accordingly the rescue medication was used. Results: A total of 100 patients received at least 2 cycles of HEC which consisted of breast carcinomas (n = 74), ovarian carcinoma (n = 13), lung carcinoma (n = 2), periampullary carcinoma (n = 3), sarcoma (n = 4), lymphoma (n = 3), and seminoma (n = 1). Anthracycline-cyclophosphamide combination for breast cancer was the most prescribed chemotherapy regimen. Forty-six patients developed breakthrough nausea/vomiting. Domperidone followed by olanzapine was the preferred rescue medications used. History of CINV in previous cycle and young age (<50 years) were the risk factors associated with breakthrough nausea vomiting in our study. Conclusion: Breakthrough nausea vomiting is a major challenge in patients receiving HEC regimen.